Identification and Characterization of Cinnamyl Alcohol Dehydrogenase Encoding Genes Involved in Lignin Biosynthesis and Resistance to Verticillium dahliae in Upland Cotton (Gossypium hirsutum L.) - Li, Haipeng; Zhang, Shulin; Zhao, Yunlei; Zhao, Xulong; Xie, Wenfei; Guo, Yutao; Wang, Yujie; Li, Kun; Guo, Jinggong; Zhu, Qian-Hao; Zhang, Xuebin; Jia, Kun-Peng; et al. (Frontiers in Plant Science, 2022)
Verticillium wilt, caused by the soil-borne fungus Verticillium dahliae, is one of the most devastating diseases in cotton (Gossypium spp.). Lignin in the cell wall forms a physical barrier to inhibit pathogen invasion, and defense-induced lignification reinforces secondary cell wall to prevent pathogens from further spreading. Cinnamyl alcohol dehydrogenases (CADs) catalyze the production of three main monolignols, p-coumaryl- (H), coniferyl- (G), and sinapyl-alcohols (S), which are the fundamental blocks of lignin. Here, we identified CAD genes in G. hirsutum, analyzed their expression profiles in cotton leaf, stem, and root from different developmental stages, and selected GhCAD35, GhCAD45, and GhCAD43, which were consistently induced by V. dahliae inoculation in G. hirsutum cultivars resistant or susceptible to V. dahliae. On the basis of confirmation of the in vitro enzymatic activity of the three proteins in generation of the three monolignols, we used virus-induced gene silencing (VIGS) to investigate the effects of silencing of GhCAD35, GhCAD45, or GhCAD43 on resistance to V. dahliae as well as on deposition and the composition of lignin. Silencing each of the three CADs impaired the defense-induced lignification and salicylic acid biosynthesis in stem, and compromised resistance to V. dahliae. Moreover, our study showed that silencing the three GhCADs severely affected the biosynthesis of S-lignin, leading to a decrease of the syringyl/guaiacyl (S/G) ratio. Heterogeneous overexpression of GhCAD35, GhCAD45, or GhCAD43 in Arabidopsis enhanced disease resistance. Taken together, our study demonstrates a role of the three GhCADs in defense-induced lignin biosynthesis and resistance to V. dahliae in G. hirsutum.